IMPLEMENTASI SISTEM PENGEN DALIAN INTERN PEMERINTAH (SPIP) DALAM MEWUJUDKAN GOOD GOVERNANCE PADA BADAN PENDAPATAN DAERAH KABUPATEN GOWA - Annisa, Melda; S, Suhendra (Patria Artha Journal of Accounting dan Financial Reporting, 2023)
This study aims to determine the implementation of PP No. 60 of 2008 concerning theGovernment Internal Control System (SPIP) at the Regional Revenue Agency of Gowa Regency by looking at the elements of SPIP, namely the control environment, risk assessment, control activities, information and communication in realizing Good Governance. This type of research is a qualitative research and Bapenda profile and interviews as data collection methods. This study also explains an Agency Theory theory. The implications of Agency Theory theory for this research, can explain the existence of the Regional Government as an institution that can be trusted to act in accordance with the public interest by carrying out its duties and functions appropriately, making financial accountability mandated to it, so that the objectives economy, public services and community welfare can be achieved optimally. The results of this study indicate that the Gowa Regency Regional Revenue Agency has implemented the five elements of the Government's Internal Control System properly and is committed to providing accountability to the community both through the reliability of financial reporting, safeguarding state assets, and compliance with laws and regulations, so as to achieveeffectiveness and efficiency in the implementation of activities carried out for the realization of good state governance, there is an increase in performance which has an impact on increasing PAD (Regional Original Income) in 2020 Rp. 1,833,160,557,136.00/ Year 2021 Rp. 1,841,411,192,535.00.